Optimizing the Quality of Human Resources by Developing Youngpreneurs with a Sharia Base - Arif, Muhammad; Hamzah, Zulfadli; Krismen, Yudi; Maulana, Ag (Yayasan Putra Adi Dharma, 2023)
The problem at hand is the low interest and ability of rural youth in entrepreneurship, as a significant portion of the community relies on limited employment opportunities in palm oil plantations. With the aim of enhancing the quality of human resources in Sungai Manasib village, the proposer intends to carry out community service activities. The proposed solution to address the partner's issues involves conducting an educational program on Sharia-based entrepreneurship, introducing Sharia financial institutions for business financing, organizing online entrepreneurship field trips, and providing digital marketing assistance to the youth/rural community of Sungai Manasib. The outcome of this dedication is expected to assist the village of Sungai Manasib in enhancing the quality of its human resources/community through the growth of youngpreneurs who operate businesses in accordance with Sharia principles, with the hope of providing a solution to the issue of unemployment in Sungai Manasib village. In addition, the mandatory output of this community service activity will be published in local mass media, and an additional output will be published in a nationally accredited Sinta 5 community service journal. The PkM activity will be carried out in several stages, starting with the planning stage, followed by counseling and mentoring, and ending with a measurable evaluation. The PkM activity has a positive impact on the improvement of human resources in the village and is able to provide more knowledge and interest for young people to engage in entrepreneurship.